Mother's sacrifice reflected in inside the kingdom by carmen bin laden (2004): a feminist approach research paper - Hidayati, Mega Nur; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi, S.S. M. Hum (2014)
The major problem of this study is how is mother's sacrifice reflected in Carmen bin Laden Inside The Kingdom. The objective if this study is to analyze the memoir based on its structural elements and to analyze the memoir based on the feminist analysis. In analyzing Inside The Kingdom, the writer use qualitative method and feminist approach. The data sources consist of primary data and secondary data sources. The primary data source is the memoir Inside The Kingdom itself and the secondary data sources are the other sources related to the analysis such as the author's biography, books of literary theory and feminism. The method of the data collection is library research. The technique of data analysis descriptive analysis. The results of the study show the following conclusions. First, from the structural analysis of the memoir it shows that Carmen bin Laden wants to convey her idea about a mother's sacrifice. Second, based on Feminist Approach, the memoir Inside The Kingdom Saudi Arabia tradition implicitly practiced that women being placed as inferior